O programa Ler e Escrever na perspectiva dos professores da rede estadual de ensino de S??o Paulo - Gimenes, Tatiane Affonso (2017)
The learning processes assumed in the recent years centrality in the debate about the educational policies related to elementary school, with the emergency of programs and projects aiming to deal this issue. Among these programs we mentioned the program Ler e Escrever from Secretary of Education of the State of S??o Paulo (SEE-SP), object of this dissertation, implemented on Education of State of S??o Paulo since 2008, as part of a large set of measures that aimed improve the education quality. Our goal was to know how a group of teachers comprehend the implementation process of this educational policies and how this comprehension is realized by them, as its impact in their work. To reach this goal, our start concern was map the recent production around the educational policies with focus on the literacy process and its implementation we used theses and dissertations that had the Program as a study object, besides the bibliography specialized produced by the education area. In sequence we did a deepening in the documentary analysis of the program Ler e Escrever, through of their official documents produced by the Secretary of Education of S??o Paulo. Finally, to verify how teachers understand this documents and how their work is impacted, we realized a set of interviewees with a group of teachers who teach in the cycle one in public schools located in the Municipality of S??o Paulo, more precisely in the North Zone, they were selected by the criterion of availability. The interview was divided by three initial topics and deal with the general education formation, the Public Educational Policies and the Program Ler e Escrever. The testimony of teachers shows the criticism to the fact of do not feel part on the elaboration of educational policies, in a general way. For this reason, they argue that although they perceive the matter and need for programs such as Ler e Escrever, focusing on elementary education one, they need to be reviewed and improved, considering the peculiarities of school contexts, and providing adequate formation for teachers.